Design, analysis and fabricate of coconut water juice extractor / Ahmad Radhee Athaillah and Ahmad Najmie Rusli - Athaillah, Ahmad Radhee; Rusli, Ahmad Najmie (School of Mechanical Engineering, 2022)
The purpose of this project is to develop, design, and fabricate a coconut juice water extractor machine to help the user extract coconut juice more efficiently. The coconut juice extractor machine gives new alternatives to people who are facing problems extracting coconut juice from the coconut. The design of this machine can be used in various aspects which is for small business or even domestic use. In this project, it is important to produce a machine that can reduce capital costs, increase the efficiency of production, have safe features, and have a good design. To achieve the project objective, there are three phases, which are designing a project, fabricating process, and testing process. The difference between this product and the current product available in the market is the material itself and add-on safety features were added. Even with better material the new product is much more economical